Limited evidence that arthroscopic femoral osteochondroplasty is better than debridement alone in femoroacetabular impingement: a systematic review. Issue 3 (6th May 2016) - Hoppe, Daniel J; Johannsen, Adam M; Safran, Marc R
Abstract : Importance: Over the past decade, there has been great interest in the application of hip arthroscopy to the treatment of femoroacetabular impingement (FAI). Recent research suggests excellent short-term and medium-term outcomes; however, these conclusions are based on non-comparative, observational studies. Objective: The purpose of this systematic review is to examine whether arthroscopic femoral osteochondroplasty leads to improved functional outcomes and higher patient satisfaction as compared with isolated soft tissue debridement in the treatment of FAI. Evidence review: EMBASE, Ovid MEDLINE and the Cochrane Central Register of Controlled Trials were searched for articles reporting on outcomes after arthroscopic treatment of FAI. Articles on debridement were included only if they explicitly stated that the procedure was performed for FAI, while those on osteochondroplasty were included only if >90% of patients underwent a femoral osteochondroplasty. Articles were assessed using the Methodological Index for Non-Randomised Studies and the Cochrane Collaboration's Risk of Bias Tool. Descriptive statistics were tabulated for demographics and outcome measures where possible. Findings: 24 studies with 2692 patients, out of 1255 articles screened, met criteria for inclusion, of which 4 reported on debridement alone, 18 reported on osteochondroplasty, and only 2 compared treatments. The majority of studies (75%) were level IV quality evidence, with no randomised trials identified. The modified Harris Hip Score (mHHS) was the most common outcome measure used, with no differences seen between groups. Of the 2 comparative studies, 1 found a significant difference in mHHS favouring osteochondroplasty, while the other did not. No studies in the debridement group reported on satisfaction, while 8 studies in the osteochondroplasty group showed high satisfaction at a range of 12–46 months postoperatively. Conclusions and relevance: There is not yet a definitive answer to the question of whether performing femoral osteochondroplasty in the treatment of FAI is better than debridement alone, and whether this will lead to decreased pain, improved long-term function or delay the onset of osteoarthritis. However, from the limited evidence available, the results of osteochondroplasty do appear to be more successful. Prospective studies comparing both treatments are required to assess whether osteochondroplasty is justified in appropriately selected individuals.